2007
DOI: 10.1097/01.nnr.0000263972.54619.4a
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Attitudes Toward Provision of Care and Related Health Outcomes

Abstract: Both attitude and social pressures had a significant impact on the intention to perform PLS, and results show the relative importance of these variables in understanding the nurse's intention to provide support. Although behavioral intent had no significant influence on behavior, as measured by the patient's length of labor, clinical significance needs to be addressed. The regression correlation suggested that as the behavioral intent scores increased, length of labor decreased in the nurse's parturient popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 16 publications
3
30
0
1
Order By: Relevance
“…After having controlled for country and past behaviour, attitudes, subjective norms and perceived behavioural control accounted for an additional 34% of the explainable variance in intention. This finding is consistent with those of previous studies, whereby the TPB has explained 68% of nurses' intention to adhere to universal precautions, 48% of health workers' intention to provide home care for HIV infected individuals, 35% of nurses' intention to care for SARS patients and 70% of nurses intended labour support [29-33]. In line with a growing body of research supporting the role of perceived moral obligations as an independent predictor of intention, moral norms contributed 2.3% to the explained variance in students' intentions after controlling for the TPB variables.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…After having controlled for country and past behaviour, attitudes, subjective norms and perceived behavioural control accounted for an additional 34% of the explainable variance in intention. This finding is consistent with those of previous studies, whereby the TPB has explained 68% of nurses' intention to adhere to universal precautions, 48% of health workers' intention to provide home care for HIV infected individuals, 35% of nurses' intention to care for SARS patients and 70% of nurses intended labour support [29-33]. In line with a growing body of research supporting the role of perceived moral obligations as an independent predictor of intention, moral norms contributed 2.3% to the explained variance in students' intentions after controlling for the TPB variables.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is congruent with findings in other studies of treatment delivery and compliance with precautions in health care workers [29-32]. This finding is also similar to that reported by Sauls [33], who identified attitudes as more influential in determining health care delivery intentions than subjective norms. In contrast, Vermette and Godin [30] found perceived behavioural control to be the strongest influencing factor of nurses' intention to provide home care for HIV infected people.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], …”
Section: Resultsmentioning
confidence: 99%
“…The former was defined as a nurse’s beliefs about working collaboratively with colleagues to deliver weight management care, and the latter as a nurse’s perceptions of role pressure to perform or not to perform weight management care. Although the relationships between TWB and PRI and weight management care have not been previously evaluated, a few studies have suggested the influence of role identity and teamwork on other healthcare behaviors, such as administration of opioids for pain relief [26] and provision of professional labor support to parturient women [34]. We therefore hypothesized that positive teamwork beliefs and professional role identity would be directly associated with more frequent professional weight management practices and higher levels of self-efficacy.…”
Section: Introductionmentioning
confidence: 99%